2020
DOI: 10.3390/jof6040327
|View full text |Cite
|
Sign up to set email alerts
|

Variable Correlation between Bronchoalveolar Lavage Fluid Fungal Load and Serum-(1,3)-β-d-Glucan in Patients with Pneumocystosis—A Multicenter ECMM Excellence Center Study

Abstract: Pneumocystis jirovecii pneumonia is a difficult invasive infection to diagnose. Apart from microscopy of respiratory specimens, two diagnostic tests are increasingly used including real-time quantitative PCR (qPCR) of respiratory specimens, mainly in bronchoalveolar lavage fluids (BAL), and serum β-1,3-d-glucan (BDG). It is still unclear how these two biomarkers can be used and interpreted in various patient populations. Here we analyzed retrospectively and multicentrically the correlation between BAL qPCR and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 24 publications
1
13
0
Order By: Relevance
“…Thus, our findings support the EORTC/MSGERC recommendations that require ≥2 consecutive serum samples to be BDG positive to diagnose probable PCP if other etiologies have been ruled out [11]. Conversely, a negative BDG result-that may be potentially false negative because of a low PJ load and low BDG release [16]-strongly suggested the absence of PCP in our patients, which was supported by either the BAL fluid sample PCR negativity or the determination of alternative etiologies (Table 1).…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Thus, our findings support the EORTC/MSGERC recommendations that require ≥2 consecutive serum samples to be BDG positive to diagnose probable PCP if other etiologies have been ruled out [11]. Conversely, a negative BDG result-that may be potentially false negative because of a low PJ load and low BDG release [16]-strongly suggested the absence of PCP in our patients, which was supported by either the BAL fluid sample PCR negativity or the determination of alternative etiologies (Table 1).…”
Section: Discussionsupporting
confidence: 78%
“…According to positive IFA or PJ -PCR results, the revised/updated EORTC/MSGERC 2008 consensus definitions of invasive fungal disease [ 11 ] allowed one to classify pneumonia episodes as proven (both IFA and PJ -PCR positive) or probable (only PJ -PCR positive) PCP episodes, respectively. In view of conflicting opinions about the role of BDG in the PCP diagnosis [ 4 , 16 , 17 ], we only used BDG results to corroborate the results obtained with the PJ -PCR assay. Furthermore, microbiological standard-of-care testing results allowed one to classify non-PCP episodes as bacterial, viral, or (outside PCP) fungal pneumonia episodes, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…The significance of detected Pneumocystis DNA using PCR alone remains uncertain, and can be due to colonization of the respiratory tract [ 37 ]. Real-time quantitative (RTqPCR) assays are the only PCR method recommended for diagnosis [ 38 ]. A study conducted in 108 critical patients with COVID-19 from the intensive care unit showed that 9.3% had positive Pneumocystis RTqPCR tests from bronchoalveolar lavage/tracheal aspirate/sputum samples [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…Serological tests for detection of anti- Pneumocystis antibodies have not proven clinically useful for establishing a diagnosis of pneumonia [ 35 , 39 ]. β-1,3-glucan is sensitive, but not specific [ 38 , 40 ]. The identification of specific biomarkers would be particularly useful, especially in patients where manipulation of the airway is limited and therefore the collection of respiratory samples is difficult.…”
Section: Discussionmentioning
confidence: 99%
“…In this context, it was suggested that a negative BG result could accurately exclude a PCP diagnosis (Held et al, 2011;Onishi et al, 2012;Alanio et al, 2016;Lahmer et al, 2017;Morjaria et al, 2019;Ideguchi et al, 2020;Szvalb et al, 2020). In contrast, other reports describe a suboptimal sensitivity of this assay, especially in HIV-negative patients (Nakamura et al, 2009;Li et al, 2015;Engsbro et al, 2019;Kato et al, 2019;Del Corpo et al, 2020;Mercier et al, 2020;Rogina and Skvarc, 2020). These discrepant results regarding the usefulness of serum BG assay in HIV-negative PCP patients could be related to the underlying condition that exposes to PCP risk.…”
Section: Introductionmentioning
confidence: 99%